OBSERVATION OF THE CONCEPT OF PROPORTION IN ARCHITECTURE USING THE PALAZZO FARNESE EXAMPLE - Safiye Irem Dizdar (European Scientific Journal, ESJ, 2013)
The topic is the multi-lateral relationship established during the process of spatial perception between the space and the observer. Spatial perception is as varied as the number of people who are making the observation and evaluation, just as the evaluation in the person’s systematizing is connected with the codes that the space physically provides (dimension, color, fabric, light, order…). Although the concept of proportion, one of the concurrences in spatial coding, dates to the ancient period, in this study the evaluations will be made using the example of a building from the Renaissance period. In Renaissance architecture which began in Florence at the beginning of the fifteenth century and spread from there to Europe by the end of the same century, religious architecture like churches, cathedrals and chapels continued and examples of civil architectural buildings like kiosks, palaces and mansions gained speed (in comparison with the buildings of the Middle Ages). While Renaissance architects took the arch, dome, column and decorative items from Greek and Roman art in organizing buildings, they remained attached to some shared values and old traditions; however, they found an opportunity to produce new and original styles. In this context the architect led the way himself in clarifying the arrangement that would be applied, the proportions and the details through the form and measurements of the building What was inescapable in Renaissance period buildings was a conceptual harmony that numbers and proportions achieved. We know that this concept that had progressed ever since Aristotle had acquired the definition that “all the elements of the universe are the elements of numbers and in this context the number of the universe is a ball of numbers and harmony.The study includes debating in Renaissance buildings the criteria for the spatial assemblage in regard to the Palazzo Farnese building.